Rigid Plastic Finite Element Analysis of Forging Process and Its Application Using Afdex Software - N. Azman, A.; A. Mohd Salleh, N.; S. Joun, M.; K. Razali, M. (International Journal of Engineering and Technology, 2018)
Metal forming has been one of the important manufacturing operations in which include variety of manufacturing processes such as forging, extrusion, drawing and sheet metal. Finite Element Analysis has been used to shows whether a product will break, wear out, or work the way it was designed. However, the current forging simulator method has its limitations in providing a good result. Among the limitation are it is not accurate in the case of stress concentrations and only have capability of one stage forging process. This research has been able to introduce the basic concept of AFDEX while analyzing cold forging process of three products which are rivet nut, flat countersunk head elevator bolt and wheel lock nut in order to define the best process design and to determine the product design for each product. Several process parameters which affect the result on the simulation has been able to analyze which are type of material and type of lubricant used. Both the parameter contributed as major factor to be consider when analyzing a product. Several defects were also identified and the countermeasure were able to found during the analysis. In conclusion, this study has been able to show significance of AFDEX software as a metal forming simulator and the simulation process has able to produce the optimal die design for the threeproducts.Â Â